2022
DOI: 10.2147/jir.s348491
|View full text |Cite
|
Sign up to set email alerts
|

p38MAPK Signaling Pathway in Osteoarthritis: Pathological and Therapeutic Aspects

Abstract: Osteoarthritis (OA) is an aging-related joint disease, pathologically featured with degenerated articular cartilage and deformation of subchondral bone. OA has become the fourth major cause of disability in the world, imposing a huge economic burden. At present, the pathogenesis and pathophysiology of OA are still unclear. Complex regulating networks containing different biochemical signaling pathways are involved in OA pathogenesis and progression. The p38MAPK signaling pathway is a member of the MAPK signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 95 publications
2
33
0
Order By: Relevance
“…Many signaling pathways are involved in the progression of OA (27)(28)(29)(30)(31)(32)(33), including NF-κB signaling pathway, JNK signaling pathway, MAPK signaling pathway, Wnt signaling pathway, PI3K/AKT/mTOR signaling pathway, and so on. Among them, NF-κB signaling pathway is reported to be involved in chondrocyte catabolism, chondrocyte survival and synovial inflammation (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many signaling pathways are involved in the progression of OA (27)(28)(29)(30)(31)(32)(33), including NF-κB signaling pathway, JNK signaling pathway, MAPK signaling pathway, Wnt signaling pathway, PI3K/AKT/mTOR signaling pathway, and so on. Among them, NF-κB signaling pathway is reported to be involved in chondrocyte catabolism, chondrocyte survival and synovial inflammation (30).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, NF- κ B signaling pathway is reported to be involved in chondrocyte catabolism, chondrocyte survival and synovial inflammation ( 30 ). And MAPK signaling pathway is reported to be play a pivotal role in inflammatory factor production and the cartilage degeneration process in OA ( 28 ). Researches on signaling pathways involved in regulating the progression of OA will provide potential therapeutic targets for OA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MTK1 was also shown to function as an oxidative-stress sensor that induces a stress-activated p38 and JNK MAPK signaling [ 27 ]. The p38 and JNK MAPK signaling is known to participate in the pathogenesis of OA through the induction of cellular senescence, the hypertrophic differentiation, the synthesis of MMPs, and the production of pro-inflammatory factors [ 29 ]. Our data suggest that the NOX system, as a major source of cellular ROS, plays an important role in the activation of p38 and JNK MAPK signaling during OA progression.…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, activated p38 regulates stress responses as well as cell growth, proliferation, differentiation, migration, and death. Activation of p38 MAPK signaling induces the expression of pro-inflammatory mediators, including COX-2 and tumor necrosis factor-α (TNF-α) [ 20 21 22 ]. Measurement of p38 phosphorylation levels in the blood monocytes of mice with endotoxemia revealed that LPS can induce p38 phosphorylation; propofol treatment could significantly inhibit p38 phosphorylation, indicating that propofol has an anti-inflammatory effect [ 8 ].…”
Section: Discussionmentioning
confidence: 99%